Trabalho destruído e funcionalização do lazer: possíveis relações em tempos de alta modernidade. - Andrade, Rafael Junio; Pereira, Eveline Torres; Vieira Botelho, Maria Izabel [UNESP]; da Silva, Silvio Ricardo (Universidade Federal do Rio Grande do Sul (UFRGS), Escola de Educação Física, 2008)
The possible relationships between leisure and labor and its association with the formation of high modernity as a historic and social phenomenon in a historic - dialectic perspective is discussed in this text. A bibliographic research on public documents such as journals, books, monographs and iconography's materials from classic and contemporary authors was carried out. It was concluded that leisure was equipped during the development of modernity and plays a revitalizing role for the labor force and construction of a discipline that is needed for a flexible and heterogeneous labor nowadays which characterize the contemporary societies.
Destroyed labor and leisure functional: possible relationships at high modernity times
Keywords: Leisure activities; Work; Postmodernism